2021
DOI: 10.1122/8.0000247
|View full text |Cite
|
Sign up to set email alerts
|

The yielding of attractive gels of nanocrystal cellulose (CNC)

Abstract: The flow behavior of nanocrystalline cellulose (CNC) hydrogels in the presence of a monovalent electrolyte (NaCl) as a function of CNC and salt concentration is explored using a variety of linear and nonlinear rheological tests. We have first observed an apparent “slip yield stress” at small wall shear stress values that is mainly due to the onset of solidlike slippage of the hydrogels before their true yielding and deformation. This flow regime and the “slip yield stress” can be eliminated using a sandpaper o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 63 publications
3
12
0
Order By: Relevance
“…We note that the viscous LB diagrams show self-intersecting loops for the biphasic and liquid crystalline phases. Self-intersecting loops have also been observed by Moud et al (2021) for highly concentrated hydrogels with cellulose nanocrystals and was attributed to an overshoot in shear stress response. The strain-stiffening (S) and shear-thickening (T) dimensionless ratios are compiled in Fig.…”
Section: Cnc Phase Bahavior From Nonlinear Oscillatory Shear Analysismentioning
confidence: 71%
See 2 more Smart Citations
“…We note that the viscous LB diagrams show self-intersecting loops for the biphasic and liquid crystalline phases. Self-intersecting loops have also been observed by Moud et al (2021) for highly concentrated hydrogels with cellulose nanocrystals and was attributed to an overshoot in shear stress response. The strain-stiffening (S) and shear-thickening (T) dimensionless ratios are compiled in Fig.…”
Section: Cnc Phase Bahavior From Nonlinear Oscillatory Shear Analysismentioning
confidence: 71%
“…10 wt% CNC, were found not to exhibit wall slip (Derakhshandeh et al 2013). Danesh et al (2021) showed that concentrations 1-5 wt% CNC obeyed the noslip boundary condition, while the addition of NaCl caused wall slip.…”
Section: Cnc Phase Bahavior From Nonlinear Oscillatory Shear Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the multiple uses those iridescent inks created by CNCs might give, it is possible that they will attract attention soon. There are other challenges as well that need proper investigation such as slip effects that affect the local organization of CNCs like other colloids 243 during a process adjacent to the walls. Investigation with this sort is largely unexplored in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematically to incorporate yielding into flow equation of the hydrogel one can add an intercept into power law equation introduced earlier to produce Herschel-Bulkley model. Several hydrogel publications in the literature have used this paradigm 88,[220][221] .…”
Section: Modelsmentioning
confidence: 99%